1997
DOI: 10.1111/j.1447-0756.1997.tb00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Studies on Matrix Metalloproteinase‐9 (MMP‐9) and Type‐IV Collagen in Endometrial Carcinoma

Abstract: Immunohistochemical staining of MMP-9 and the type-IV collagen was performed on paraffin sections of endometrial carcinoma. Immunostaining in 129 cases of endometrial cancer detected MMP-9 in 19.0% of the cases. MMP-9 positive was shown in 30% of the cases with vessel invasion, and in 12.7% of the cases without vessel invasion (p < 0.05). MMP-9 showed positive in many cases with poor differentiation and lymph node metastasis, but still failed to achieve statistical significance. MMP-9 staining did not correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…The data suggest that these MMPs are produced more frequently and in greater quantities as EC progresses, and hence that a degradation of interstitial stroma and subendothelial basement membrane is more intense with progression. Data on MMP-9 partly agree with those of Inoue et al [17], who showed by immunohistochemistry that expression was associated with vessel invasion, G3 and lymph node metastasis. They could explain the greater dissemination and deepening of EC cells into the myometrial wall as they undergo transition from G1 to G3.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data suggest that these MMPs are produced more frequently and in greater quantities as EC progresses, and hence that a degradation of interstitial stroma and subendothelial basement membrane is more intense with progression. Data on MMP-9 partly agree with those of Inoue et al [17], who showed by immunohistochemistry that expression was associated with vessel invasion, G3 and lymph node metastasis. They could explain the greater dissemination and deepening of EC cells into the myometrial wall as they undergo transition from G1 to G3.…”
Section: Discussionsupporting
confidence: 89%
“…In endometrial carcinoma (EC), however, knowledge is circumstantial. Angiogenesis is associated with tumour changeover [15] and poor histological differentiation, or grade 3 [16], and MMP-9 is overexpressed in grade 3 and metastatic tumours [17]. We therefore looked for angiogenesis extent and MMP-2 and MMP-9 mRNA expression in EC biopsies belonging to a pathway of progression, as de®ned by histological grades and depth of myometrial invasion.…”
Section: Introductionmentioning
confidence: 99%
“…MT1-MMP plays an essential role in invasion and metastasis in most cancer types through activation of pro-MMP-2 and digestion of ECM macromolecules by these MMPs [100]. Such results were confirmed by numerous other studies, showing that MMP-2 and MMP-9 detected by in situ hybridization were significantly overexpressed in cases of increased histological grade carcinomas, being also associated with increasing depth of myometrial invasion [101], vessel invasion, and lymph node metastasis [60, [102][103][104]. Aglund et al [105] found that both gelatinases (MMP-2 and -9) correlated with the histological grade, but only MMP-9 correlated with the disease clinical stage.…”
Section: Role Of Mmps In Uterine Cancersupporting
confidence: 76%
“…Epithelial ovarian carcinoma MMP-2 expression correlates with higher tumor grade, staging and recurrence rate [48,[75][76][77] Primary cervical carcinoma Immunoreactivity of MMP-2 correlates with depth of myometrial invasion, pelvic lymph node metastasis and tumor vascularity [92,93] Endometrial carcinoma MMP-2 expression associates with depth of myometrial invasion and lymph node metastasis [60, [101][102][103][104] MMP-26 and TIMP-4 expression correlates with deeper myometrial invasion and grade 3 lesions [14] Low TIMP-2 expression correlates to myometrial invasion, lymphovascular space involvement and lymph node metastasis [103] High grade UEC MMP-7 expression correlates with shorter disease-free intraval, tumor invasion and metastasis [112] UEC: Uterine endometrial carcinoma.…”
Section: Malignancy Correlation Of Selected Mmp/timpmentioning
confidence: 99%
“…Furthermore, the frequency of MMP‐2 and MMP‐9 expression increases with advancing histologic grade and with increasing depth of myometrial invasion 22. Studies on MMP immunolocalization in endometrial carcinoma are limited: matrilysin (MMP‐7) was localized predominantly to carcinoma cells,19 MMP‐2, MMP‐1, and TIMP‐1 proteins were correlated with histologic stage, depth of infiltration, histologic type and age,23 while MMP‐9 proteins were mainly localized to tumor cells 24. Studies have localized TIMP‐1 mRNA to the stromal compartment of the malignant endometrium, while TIMP‐2, TIMP‐3, and MT1‐MMP mRNA have been localized to both the stromal and epithelial compartments 20.…”
mentioning
confidence: 99%